Prototype of implementation of hybrid visible light communication technology for tele controlling systems in archives warehouse - Yurike Aditya Eka Putri; Amalia Eka Rakhmania; Azam Muzakhim Imammuddien (Jurnal Jaringan Telekomunikasi, 2022)
Paper is one type of archive that is stored in the Archives Building. Maintenance of paper type archives needs to be considered to avoid mold growth and discoloration due to cigarette smoke. Therefore, a telecontrolling device is needed that can maintain a stable air humidity at 30% - 55% and a temperature of 15 °C - 22 °C. However, devices with a frequency of 2.4 GHz should not be used simultaneously in the same area because it will cause interference that can reduce performance. In this study, a temperature tele controlling system and smoke detection in the archive warehouse were made using hybrid visible light communication technology to improve data transmission performance. The system consists of 1 transmitter node connected to DHT 22, MQ 2, LED laser and WiFi network, as well as 2 receiver nodes to control the fan and water pump. The data from the receiver will be passed through the photodiode and then processed by the microcontroller. If the temperature value reaches the threshold, the receiver node will send a command so that the fan will turn on automatically, then if the smoke value reaches the threshold, the water pump will turn on automatically. The temperature and smoke values ??can be monitored in real time through the android application. The test results show that the use of hybrid visible light communication technology in the tele controlling system makes the delivery performance better.